2007
DOI: 10.1128/jvi.02300-06
|View full text |Cite
|
Sign up to set email alerts
|

Spindles of an Entomopoxvirus Facilitate Its Infection of the Host Insect by Disrupting the Peritrophic Membrane

Abstract: The mode of action by which entomopoxvirus (EPV) spindles, proteinaceous crystalline bodies produced by EPVs, enhance EPV infection has not been clarified. We fed Anomala cuprea EPV (AcEPV) spindles to host insects; subsequent scanning electron microscopy revealed the disruption of the peritrophic membranes (PMs) of these insects. The PM is reportedly a barrier against the infection of some insects by viruses. Quantitative PCR of AcEPV DNA in the ectoperitrophic area revealed that PM disruption facilitated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 27 publications
0
39
0
1
Order By: Relevance
“…Litomosoides chagasfilhoi microfilariae can invade the midgut epithelium during PM development of Culex quinquefasciatus, but when the PM was fully formed, microfilariae were no longer able to cross it (Santos et al, 2006). On the other hand, it may belong to the third strategy as Mitsuhashi et al (2007) demonstrated that fusolin, the constitutive protein of the spindles of entomopoxvirus, may bind with chitin in the PM, thus enhancing disruption in the host insect. In larval Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Litomosoides chagasfilhoi microfilariae can invade the midgut epithelium during PM development of Culex quinquefasciatus, but when the PM was fully formed, microfilariae were no longer able to cross it (Santos et al, 2006). On the other hand, it may belong to the third strategy as Mitsuhashi et al (2007) demonstrated that fusolin, the constitutive protein of the spindles of entomopoxvirus, may bind with chitin in the PM, thus enhancing disruption in the host insect. In larval Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Infected cells were harvested 72 h postinoculation. Preliminary Western blot analysis results using an antibody to the AncuEPV spindles (26) indicated that the recombinant fusolin was contained only in the insoluble fraction of infected cells. Therefore, protein purification was performed under a denaturing condition as described below.…”
Section: Viruses and Insects Propagation Methods Of Ancuepv Andmentioning
confidence: 99%
“…Precision Plus all blue standard (Bio-Rad, Hercules, CA) was used as molecular mass standard. For Western blot analysis, protein samples were run on a low-bis polyacrylamide gel and blotted onto a polyvinylidene difluoride (PVDF) membrane (FluoroTrans; (26) in Tris-buffered saline containing 0.05% Tween 20 at room temperature for 1 h. Binding of the antibody was probed with alkaline phosphatase-conjugated goat anti-mouse immunoglobulin G (Promega, Madison, WI) and visualized using a 5-bromo-4-chloro-3-indolylphosphate-nitroblue tetrazolium (BCIP-NBT) solution kit for alkaline phosphatase staining (Nakalai Tesque, Tokyo, Japan).…”
Section: Viruses and Insects Propagation Methods Of Ancuepv Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusolin was demonstrated to form spindle-like bodies that enhance the entomopoxvirus oral infection in host larvae. The mechanism of action for these spindles appears to be associated with the disruption of the peritrophic membrane (PM) allowing the virions to reach the midgut epithelial cells (Mitsuhashi et al, 2007). Except for the case of CfDEFMNPV (Li et al, 2000), in baculoviruses no spindle bodies have been observed, although GP37 was found to be associated with OBs in AcMNPV (Vialard et al, 1990).…”
Section: Genes Affecting the Insect Host As An Organismmentioning
confidence: 99%